Sustainable one-part alkali activated slag/fly ash Geo-SIFCOM containing recycled sands: Mechanical, flexural, durability and microstructural properties - Köksal, Fuat; Türkoğlu, Mesut; Bayraktar, Oğuzhan Yavuz; Bozkurt, Tevfik Hakan; Benli, Ahmet; Kaplan, Gökhan (Elsevier BV, 2023)
Slurry Infiltrated Fiber Concrete or Composite (SIFCOM) is a unique form of steel-fiber-reinforced cement composite that possesses exceptional toughness and superior mechanical properties like compressive, shear, tensile, and flexural strengths. New supplies of fine aggregate are required since the construction industry is experiencing natural sand shortage. By thoroughly evaluating workability, mechanical properties, flexural toughness, durability and microstructure, this study demonstrates the potential of various recycled sands from different sources in the manufacture of sustainable slag/fly ash one-part alkali activated SIFCOM (Geo-SIFCOM). Recycled concrete, brick and ceramic sands were used as a substitute of 10, 25 and 50% by volume of silica sand. Steel fiber ratios of 5%, 10%, and 15% were used and exposed to heat curing for 6, 24 and 48 h at 80 °C. Taguchi method was used to investigate the optimum mixture. The results showed that 24 h heat-cured mixture containing 25% recycled concrete sand and 15% fiber (C25F15) had the largest compressive strengths of 68.49 MPa, 74.53 MPa and 80 MPa at 7, 28, and 91 days, respectively. All 6 h – cured mixtures containing 100% slag exhibited the best resistance to freeze-thaw and the mixtures heat cured for 6 h demonstrated the best compressive strength resistance to elevated temperature and F-T cycles regardless of FA content. The largest flexural toughness was also assessed for the mixture with 50% brick sand and 15% fiber (B50F15) heat-cured for 6 h. The mixture with 50% FA and 50%slag (50% ceramic sand and 15% fiber) exhibited the best high temperature resistance.